Живцювання троянд на різних субстратах в умовах Кременецького ботанічного саду - Скоропляс, Ірина; Skoroplyas, Iryna (Східноєвропейський національний університет імені Лесі Українки, 2016)
Наведено результати вегетативного розмноження троянд, перспективних для використання в декоративно- промисловому розсадництві. Розглянуто дію регуляторів росту на укорінення зелених живців для прискореного отримання посадкового матеріалу. Установлено, що застосування стимуляторів росту «Корневін» дає кращі результати, порівняно із застосуванням «Епіному» й «Гетероауксину» та контролем при розмноженні троянд зеленими живцями. The results of micropagation rose promising for use in decorative and industrial nursery. We consider the effect of growth regulators on the basis of pyridine derivatives on the rooting of green cuttings roses of the accelerated receipt of planting material. Found that the use of growth promoters of the Kornevin yields better results than the Epinomu and Heteroauksun and the control of reproduction in the green roses from cuttings. Results showed the highest grade «Wartburg», and the lowest – «Vohni majaka». It should also be noted that the process took root quickly in all grades in the substrate peat + sand + leaf soil and in the treated cuttings «Kornevinom» rooting process went faster and were more rooted cuttings.
Cuttings Roses on Different Substrate in Kremenets Botanical Garden
Keywords: вегетативне розмноження; субстрат; троянда; зелене живцювання; cloning; substratum; rose; green cuttings